Corrosion-resistant, self-cleaning and super-wetting composite coating and preparation method and application thereof
Through the combination technology of peptic acid-derived compounds, oxidants and n-butyl titanate, a corrosion-resistant and self-cleaning composite coating is constructed, solving the problem of poor stability of existing coatings in corrosive environments, and achieving super-immersion and resistance Corrosion and self-cleaning effect and suitable for industrial applications.
Patent Information
- Application Number
- CN202410430754.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-11
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-04-11
AI Technical Summary
Existing superimper coatings have poor stability in corrosive environments, resulting in obstacles in large-scale applications.
The aqueous solution of the pentonic acid and/or the pentonic acid-derived compound and the oxidant is used as the bionic adhesion coating, and combined with the n-butyl titanate solution diluted with an organic solvent as the bionic mineralized coating. The bridge and mineralization reaction of polyphenol molecular bridges are constructed. Corrosion-resistant, self-cleaning composite coating.
The super-wetting, corrosion resistance and self-cleaning properties of the coating are realized, and the oil and water mixture can be separated on the porous medium and anti-fog on the dense medium. The preparation method is simple, environmentally friendly, and low-cost, which is suitable for large-scale production.
Smart Images

Figure CN118325182B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite coatings, and in particular to a corrosion-resistant, self-cleaning and super-wetting composite coating and a preparation method and application thereof. Background Art
[0002] In nature, many animal and plant surfaces exhibit unique super-wetting properties, including fish scales, shark skin, and cacti, which give them unique physical and chemical properties. With the continuous deepening of the exploration of the special wetting mechanism of animal and plant surfaces, some artificial materials with special wettability have been continuously developed and widely used in the fields of oil-water separation, anti-biological adhesion, anti-icing and anti-fogging, and self-cleaning. In recent years, through a series of technologies such as chemical etching, electrospinning, template method, photolithography, sol-gel process, and coating process, the surfaces of different substrate materials have super-wetting properties, thereby obtaining the functional properties of typical biological surfaces. Among these research methods, the coating process has the characteristics of low cost, simple operation, no restrictions on different substrates, and easy large-scale production, making it an ideal super-wetting surface preparation technology. Natural plant polyphenols inspired by biotechnology can form multifunctional coatings that are independent of the substrate and have been widely used in many fields such as ecological protection, biomedicine, and petrochemicals. However, the long coating time and poor stability in corrosive environments hinder the large-scale application of these coatings. Summary of the invention
[0003] In view of the above problems, the present invention aims to provide a corrosion-resistant, self-cleaning and super-wetting composite coating and a preparation method and application thereof.
[0004] The technical solution of the present invention is as follows:
[0005] In one aspect, a method for preparing a corrosion-resistant, self-cleaning and super-wetting composite coating is provided, comprising the following steps:
[0006] S1: preparing a substrate material, a bionic adhesive coating and a bionic mineralized coating; the bionic adhesive coating is an aqueous solution of gallic acid and / or a gallic acid derivative compound and an oxidant, and the bionic mineralized coating is a solution of n-butyl titanate diluted with an organic solvent;
[0007] S2: immersing the base material in the bionic adhesive coating, taking it out, washing it, and drying it to obtain a base material coated with a polyphenol molecular bridge;
[0008] S3: immersing the base material coated with the polyphenol molecular bridge in the bionic mineralization coating, taking it out, washing it, and drying it to obtain the composite coating.
[0009] Preferably, in step S1, the concentration of the gallic acid and / or gallic acid derivative compound in the aqueous solution is 0.05-10 mg / mL, and the concentration of the oxidant in the aqueous solution is 0.05-5 mg / mL.
[0010] Preferably, the oxidant is an inorganic oxidant.
[0011] Preferably, the inorganic oxidant is an oxygen-containing acid of a halogen and its salts or peroxyacids.
[0012] Preferably, in step S1, the concentration of the solute in the n-butyl titanate solution is 0.01-10 mg / mL.
[0013] Preferably, the organic solvent is one or more of anhydrous methanol, anhydrous ethanol, n-hexane, cyclohexane, petroleum ether or oleic acid.
[0014] Preferably, in step S2 and step S3, water and ethanol are used to wash repeatedly for several times during washing.
[0015] Preferably, in step S1, when preparing the base material, a step of cleaning the base material is also included.
[0016] On the other hand, a corrosion-resistant, self-cleaning and super-wetting composite coating prepared by any of the above-mentioned preparation methods and its application in ecological protection, biomedicine and petrochemical industry are also provided.
[0017] The beneficial effects of the present invention are:
[0018] On the one hand, the composite coating of the present invention has the characteristics of super-wetting, that is, super-hydrophilic in air and super-oleophobic underwater; it has the characteristics of corrosion resistance, that is, it can resist chemical corrosion; it has the characteristics of self-cleaning, that is, it can self-clean by photocatalysis. The composite coating applied to the surface of porous media can be used for separation of oil-water layered mixtures, corrosive oil-water layered mixtures, surfactant-stabilized water-in-oil emulsions, and surfactant-stabilized corrosive water-in-oil emulsions; the coating applied to the surface of dense media can prevent fogging.
[0019] On the other hand, the preparation method of the present invention is simple, reliable, green and environmentally friendly, is not picky about the substrate, and can construct a unique micro-nano structure without the need to add nanomaterials separately. The entire process is carried out at room temperature and under normal conditions, without complex chemical reactions and the generation of no toxic by-products. The raw materials are cheap and easily available, the cost is low, and no complex and expensive instruments and equipment are required. It can be mass-produced, has a wide range of practical application value, and is conducive to industrial application and promotion. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0021] Figure 1 This is a schematic diagram of the scanning electron microscope observation results of Example 1;
[0022] Figure 2 This is a schematic diagram of the scanning electron microscope observation results of Example 2;
[0023] Figure 3 This is a schematic diagram of the scanning electron microscope observation results of Example 3;
[0024] Figure 4 This is a schematic diagram of the scanning electron microscope observation results of Example 4;
[0025] Figure 5 This is a schematic diagram of the scanning electron microscope observation results of Comparative Example 1;
[0026] Figure 6 This is a schematic diagram of the scanning electron microscope observation results of Comparative Example 2;
[0027] Figure 7 This is a schematic diagram of the scanning electron microscope observation results of Comparative Example 3;
[0028] Figure 8 This is a schematic diagram of the scanning electron microscope observation results of Comparative Example 4;
[0029] Fig. 9 ATR-FTIR results of Example 1, Comparative Example 2 and Comparative Example 4 are shown in FIG.
[0030] Fig.10 The water contact angle in air of Examples 1-4 and Comparative Example 4 changes dynamically over time;
[0031] Fig.11 Graph showing the contact angles of Example 1 to different types of oils under water;
[0032] Fig.12 This is a schematic diagram of the underwater dirt repellent and anti-fouling of Example 1;
[0033] Fig.13 This is a schematic diagram of the contact angle results of Example 1 when continuously immersed in HCl solution for 240 hours;
[0034] Fig.14 This is a schematic diagram of the contact angle results of Example 1 after continuous immersion in NaOH solution for 240 hours;
[0035] Fig.15 This is a physical picture of comparative example 2 and example 1 immersed in 1M sodium hydroxide solution;
[0036] Fig.16 The physical pictures and optical microscope pictures of the emulsion before and after separation in Example 1;
[0037] Fig.17 The figure shows the separation flux and separation efficiency of different types of oil-in-water emulsions in the examples. DETAILED DESCRIPTION
[0038] The present invention is further described below in conjunction with the accompanying drawings and embodiments. It should be noted that, in the absence of conflict, the embodiments in this application and the technical features in the embodiments can be combined with each other. It should be noted that, unless otherwise specified, all technical and scientific terms used in this application have the same meanings as those generally understood by those of ordinary skill in the art to which this application belongs. The words "including" or "comprising" and the like used in the disclosure of the present invention mean that the elements or objects appearing before the word cover the elements or objects listed after the word and their equivalents, without excluding other elements or objects.
[0039] In one aspect, the present invention provides a method for preparing a corrosion-resistant, self-cleaning and super-wetting composite coating, comprising the following steps:
[0040] S1: preparing a substrate material, a bionic adhesive coating and a bionic mineralized coating; the bionic adhesive coating is an aqueous solution of gallic acid and / or a gallic acid derivative compound and an oxidant, and the bionic mineralized coating is a solution of n-butyl titanate diluted with an organic solvent.
[0041] In a specific embodiment, when preparing the base material, a step of cleaning the base material is also included. Optionally, the base material is cleaned by soaking in ethanol for 10 to 30 minutes.
[0042] In the above embodiment, by cleaning the base material, impurities on the surface of the base material can be removed, thereby enhancing the stability of the coating in the subsequent steps and improving the quality of the composite coating. It should be noted that if the base material itself is very clean, it is not necessary to clean it. In addition, in addition to using ethanol cleaning, other cleaning methods in the prior art can also be used, such as ultrasonic cleaning.
[0043] In a specific embodiment, the cleaned substrate material is soaked in ethanol for use. It should be noted that only the hydrophobic substrate material needs to be soaked in ethanol after cleaning, so that the hydrophobic substrate material can be wetted by the coating in the subsequent steps. Other similar solvents such as methanol can also be used for soaking.
[0044] In a specific embodiment, the substrate material is a porous medium or a dense medium. Optionally, the porous medium is an organic porous medium such as polytetrafluoroethylene membrane, polyvinylidene fluoride membrane, polyurethane sponge, or an inorganic porous medium such as stainless steel mesh, inorganic ceramic membrane, and the dense medium is glass, silicon wafer, etc.
[0045] In a specific embodiment, the concentration of the gallic acid and / or gallic acid derivative compound in the aqueous solution is 0.05-10 mg / mL, and the concentration of the oxidant in the aqueous solution is 0.05-5 mg / mL.
[0046] In a specific embodiment, the oxidant is an inorganic oxidant. Optionally, the inorganic oxidant is an oxygen-containing acid of a halogen (chlorine, bromine, iodine) and its salts (such as sodium periodate, etc.) or a peroxyacid (such as ammonium persulfate, etc.).
[0047] When preparing the bionic adhesive coating, the gallic acid and / or the gallic acid derivative compound and the oxidant are sequentially added into water at 10-70° C. to be fully dissolved. Since the gallic acid and / or the gallic acid derivative compound have carboxyl groups, the dissolved aqueous solution can be rapidly oxidized by the oxidant under acidic conditions without adjusting the pH value, so that the hydroxyl groups carried by the gallic acid and / or the gallic acid derivative compound are oxidized to quinones and then to carboxyl groups and gradually form polyphenol molecular bridges. Since the polyphenol molecular bridge has a dopamine-like structure, it has strong adhesion and can be adhered to the substrate material.
[0048] It should be noted that the appropriate temperature is not only conducive to the dissolution of gallic acid and / or gallic acid derivatives, but also conducive to the self-polymerization of gallic acid and / or gallic acid derivatives under the action of oxidants, and the preparation temperature of the corresponding biomimetic adhesive coating is different for different types of oxidants. Those skilled in the art can also use high-frequency ultrasound to regulate. In addition, in addition to the oxidants used in the above embodiments, other oxidants in the prior art that can achieve the function of oxidizing gallic acid and / or gallic acid derivatives to form polyphenol molecular bridges can also be applied to the present invention.
[0049] In a specific embodiment, the concentration of the solute in the n-butyl titanate solution is 0.01-10 mg / mL.
[0050] In a specific embodiment, the organic solvent is one or more of anhydrous methanol, anhydrous ethanol, n-hexane, cyclohexane, petroleum ether or oleic acid.
[0051] In a specific embodiment, when preparing the biomimetic mineralized coating, tetrabutyl titanate is rapidly added to an organic solvent at 0-40° C. and mixed thoroughly to obtain the biomimetic mineralized coating. It should be noted that a suitable temperature is conducive to rapid and uniform mixing of tetrabutyl titanate in an organic solvent. In order to accelerate mixing, those skilled in the art may also use other means such as ultrasonic dispersion or stirring for regulation.
[0052] S2: immersing the base material in the bionic adhesive coating, taking it out, washing it, and drying it to obtain a base material coated with a polyphenol molecular bridge.
[0053] S3: immersing the base material coated with the polyphenol molecular bridge in the bionic mineralization coating, taking it out, washing it, and drying it to obtain the composite coating.
[0054] In this step, the surface of the base material treated with the bionic adhesion coating is uniformly coated with the polyphenol molecular bridge rich in carboxyl and hydroxyl groups, and the main component of the bionic mineralization coating is tetrabutyl titanate, so that the bionic mineralization coating and the base material coated with the polyphenol molecular bridge undergo chelation coordination with the hydroxyl groups on the polyphenol molecular bridge and stable bonding with the carboxyl groups through the tetravalent titanium reaction, which is the key to bionic mineralization to produce titanium dioxide micro-nanostructures. The precise mineralization of the polyphenol molecular bridge enables the inorganic nanomaterial to grow stably on the coating, which not only brings self-cleaning properties to the composite coating, but also solves the defect that the polyphenol molecular bridge is not corrosion-resistant.
[0055] In a specific embodiment, the immersion time in step S2 and step S3 is 10 to 100 minutes and 30 to 600 seconds respectively; and the washing is performed by repeatedly washing with water and ethanol for several times.
[0056] In the present invention, the coating of the bionic adhesive coating on the base material (substrate) is the key to the construction of the composite coating. Gallic acid and / or gallic acid derivative compounds are rapidly oxidized and self-polymerized under the action of an oxidant to form a polyphenol supramolecular adhesion network (polyphenol molecular bridge). The stable coating of the polyphenol molecular bridge on the substrate not only brings super wettability, but also provides reaction sites for the subsequent mineralization step; the bionic mineralization coating is continuously coated on the substrate that has been coated with the polyphenol molecular bridge to finally construct the composite coating. The hydroxyl groups on the polyphenol molecular bridge can produce polyphenol metal chelate coordination with the titanium in the bionic mineralization coating. In addition, gallic acid and / or gallic acid derivative compounds will produce a large number of carboxyl groups after being oxidized by an oxidant. A large number of carboxyl groups can quickly react with n-butyl titanate to form a carboxy-titanium reaction, which is the key to bionic mineralization to produce titanium dioxide micro-nanostructures. The precise mineralization of the polyphenol molecular bridge enables the inorganic nanomaterial to grow stably on the coating, which not only brings self-cleaning properties to the composite coating, but also solves the defect that the polyphenol molecular bridge is not corrosion-resistant.
[0057] On the other hand, a corrosion-resistant, self-cleaning and super-wetting composite coating prepared by any of the above-mentioned preparation methods and its application in ecological protection, biomedicine and petrochemical industry are also provided.
[0058] Example 1
[0059] A corrosion-resistant, self-cleaning and super-wetting composite coating is prepared by the following steps:
[0060] (1) Cut the polyvinylidene fluoride membrane into a square of 5.0 cm × 5.0 cm, clean it in an ultrasonic cleaner for 10 min, and then place it in an ethanol solution for later use;
[0061] (2) preparing a biomimetic adhesive coating, specifically: adding 0.1 g of 3,4,5-trihydroxybenzoic acid and 0.04 g of sodium periodate into 20 mL of water (water temperature 25° C.) in sequence and fully dissolving them under ultrasound;
[0062] (3) immersing the cleaned polyvinylidene fluoride membrane in the bionic adhesive coating, and placing it in a constant temperature water bath oscillator (the temperature is adjusted to 25° C.) and oscillating at a constant speed of 100 r / min. After 60 minutes, taking it out, washing it, and drying it to obtain a polyphenol molecular bridge-coated polyvinylidene fluoride membrane;
[0063] (4) preparing the biomimetic mineralized coating, specifically: at room temperature of 25° C., 0.1 g of tetrabutyl titanate was quickly added into 20 mL of anhydrous ethanol and mixed thoroughly;
[0064] (5) Immersing the polyvinylidene fluoride membrane coated with the polyphenol molecular bridge obtained in step (3) in the bionic mineralization coating and allowing it to stand for 60 seconds, taking it out, washing it, and drying it to obtain a polyvinylidene fluoride membrane with a composite coating having corrosion resistance, self-cleaning properties, and super wettability.
[0065] Example 2
[0066] Different from Example 1, the immersion time of the substrate material in step (5) of this example is 30 seconds.
[0067] Example 3
[0068] Different from Example 1, the immersion time of the substrate material in step (5) of this example is 300 seconds.
[0069] Example 4
[0070] Different from Example 1, the immersion time of the substrate material in step (5) of this example is 600 seconds.
[0071] Example 5
[0072] Different from Example 1, the oxidants in step (2) of this example are ammonium persulfate, hydrogen peroxide, sodium persulfate, and potassium periodate, respectively.
[0073] Example 6
[0074] Different from Example 1, the temperatures in step (2) and step (3) of this example are 10°C, 20°C, 30°C, 40°C, 50°C, 60°C, and 70°C, respectively, to prepare 7 different coatings.
[0075] Example 7
[0076] Different from Example 1, in step (3) of this example, the immersion time of the base material is 10 min, 20 min, 30 min, 40 min, 50 min, 70 min, 80 min, 90 min and 100 min, respectively, to prepare nine different coatings.
[0077] Example 8
[0078] Different from Example 1, the substrate materials in step (1) of this example are polypropylene film, polytetrafluoroethylene film, stainless steel mesh, nylon film, tempered glass, goggles, and polyurethane foam.
[0079] Example 9
[0080] Different from Example 1, the temperatures in step (4) and step (5) are 0°C, 10°C, 20°C, 30°C and 40°C, respectively, to prepare 5 different coatings.
[0081] Example 10
[0082] Different from Example 1, in step (2), the concentrations of 3,4,5-trihydroxybenzoic acid in the mixture were 0.05, 2, 4, 6, 8 and 10 mg / mL, respectively, to prepare 6 different coatings.
[0083] Embodiment 11
[0084] Different from Example 1, the concentrations of sodium periodate in step (2) were 0.05, 1, 3, 4, and 5 mg / mL, respectively, to prepare five different coatings.
[0085] Example 12
[0086] Different from Example 1, the concentrations of the solute in the ethanol solution of n-butyl titanate in step (3) are 0.01, 0.1, 2, 4, 6, 8, and 10 mg / mL, respectively, to prepare 7 different coatings.
[0087] Comparative Example 1
[0088] Different from Example 1, in this comparative example, no 3,4,5-trihydroxybenzoic acid is added in step (2).
[0089] In this comparative example, a single variable is maintained, and the result of using this method is more accurate than using the coating obtained by steps (1), (4) and (5) as the comparative example.
[0090] Comparative Example 2
[0091] Different from Example 1, tetrabutyl titanate is not added in step (4) in this comparative example.
[0092] In this comparative example, a single variable is maintained, and the result of using this method is more accurate than using the coating obtained by steps (1), (2), and (3) as the comparative example.
[0093] Comparative Example 3
[0094] Different from Example 1, in this comparative example, steps (4) to (5) are performed first, and then steps (2) to (3) are performed.
[0095] Comparative Example 4
[0096] Different from Example 1, this comparative example does not perform steps (2) to (5).
[0097] Test Example 1
[0098] The coatings prepared in Examples 1-4 and Comparative Examples 1-4 were observed using a scanning electron microscope. Figures 1 to 8 As shown. Figures 1 to 8 It can be seen that the surface of Example 1 is rough and a large number of nanoparticles are continuously and evenly distributed, more nanoparticles begin to appear on the surface of Example 2, the surface nanospheres of Example 3 fill the entire field of view and fill the pores of the membrane, and the surface pores of Example 4 are completely covered and have a few large-sized particles. The coatings prepared in Examples 1-4 constitute a unique titanium dioxide nano armor structure. The introduction of titanium dioxide nano armor not only increases the roughness of the polymer film, but also further adjusts the pore size of the membrane, so that it can be used for efficient oil-water emulsion separation and photocatalytic self-cleaning. The surface of Comparative Example 1 is smooth and intermittently distributed with a few nanospheres, the surfaces of Comparative Examples 2 and Comparative Examples 4 are very smooth and no nanoparticles are seen, and Comparative Example 3 exchanges the coating order of the bionic adhesion coating and the bionic mineralization coating. The surface morphology is similar to that of Comparative Example 1, and the surface nanoparticles are discontinuous. It can be seen that the bionic adhesion coating and the bionic mineralization coating and the order of their coating jointly determine the microscopic morphology of the coating.
[0099] Test Example 2
[0100] The coatings prepared in Example 1, Comparative Example 2 and Comparative Example 4 were tested by Fourier transform infrared spectroscopy with a detection range of 4000 cm -1 -400cm -1 , ATR-FTIR spectrum results are as follows Fig. 9 As shown. Fig. 9 It can be seen that the coatings prepared in Example 1 and Comparative Example 2 have a -1 There is a new broad absorption band at 3150-3600cm (no in Comparative Example 4), which is attributed to the OH stretching vibration. -1 The width of the absorption band at 500-700 cm is a sign of intramolecular hydrogen bonding, which indicates that the TiO2 nano-armor introduced by mineralization increases the hydrophilicity of the modified film. -1 There is a new broad absorption band at low frequency, which can be attributed to the Ti–O bonds in the TiO2 nanoarmor. According to the ATR-FTIR spectrum of Comparative Example 2, 1717 cm -1 、1340cm -1 and 1017cm -1 The new absorption peaks at 400 nm and 400 nm are attributed to the C=O stretching vibration of the carboxylic acid group, the OH bending vibration of the phenolic group, and the CO stretching vibration of the carboxylic acid group, respectively, proving that a large number of carboxyl groups have been introduced on the surface of the substrate material. The existence of these new peaks strongly confirms that the biomimetic adhesive coating and biomimetic mineralization coating have successfully introduced TiO2 nano-armor.
[0101] Test Example 3
[0102] The coatings prepared in Examples 1-4 and Comparative Examples 1-4 were evaluated for their underwater wetting properties using a contact angle meter and a dynamic wetting process. Some of the results are shown in Table 1. Fig.10 and Fig.11 As shown. Fig.10 It can be seen that in air, the coatings prepared in Examples 1-4 are more hydrophilic than the coating prepared in Comparative Example 4, with a smaller water contact angle and a shorter wetting time. Fig.11 It can be seen that, underwater, the coating prepared in Example 1 has water oleophobicity to various oils, including diesel, ethylene dichloride, soybean oil, cyclohexane and crude oil, and the contact angles of different types of oil droplets are all greater than 155 degrees. Therefore, the coating prepared in Example 1 has super hydrophilicity-underwater super oleophobicity super wetting properties. The coatings prepared in Comparative Examples 1-4 have contact angles of less than 145 degrees for various oils underwater, and therefore do not have underwater super oleophobic properties.
[0103] The test results of the antifouling and antifouling performance of the coating of Example 1 are as follows: Fig.12 As shown. Fig.12It can be seen that when 5 μL of light / heavy oil droplets come into contact with the coating surface, no obvious diffusion phenomenon occurs, and the oil droplets can completely leave. After several squeezing-separation cycles (even if they are severely squeezed to the point of severe deformation), the oil droplets / water droplets still remain on the needle tip, and none of them adhere to the surface of the coating prepared in Example 1. When the coatings prepared in Comparative Examples 1-4 are subjected to the same antifouling and repellent performance test, the oil droplets all adhere to the coating surface, so the coating prepared by the present invention has excellent antifouling performance.
[0104] Test Example 4
[0105] After soaking in alkaline (1M NaOH), salt (2M NaCl) or acidic (1M HCl) solutions for a long time, the wetting properties and surface morphology of the coatings prepared in Example 1 and Comparative Examples 1-3 were monitored. The contact angle results of Example 1 after continuous soaking in HCl solution and NaOH solution for 240 hours are as follows: Fig.13 and Fig.14 shown.
[0106] After the corrosion immersion test, Fig.15 As shown, the coating surface prepared in Example 1 maintained its uniform nano-armor structure and yellow-brown color, reflecting excellent stability and durability. In addition, even after 25 minutes of ultrasonic treatment, the wetting properties did not weaken. The nano-armor decorative film also exhibits chemical durability, so its wetting properties remain unchanged after the film is immersed in different corrosive solutions for 240 hours. However, after the same experiment, the light brown part of the coating prepared in Comparative Example 2 faded, and the coating also partially fell off from the surface of the film, indicating poor mechanical stability and durability. It is worth noting that the color of the solution turns yellow in NaOH solution (pH = 14), which means that the polyphenol molecular bridge is unstable in alkaline solution. The coating prepared in Comparative Example 1 is light white. Although the surface color did not change significantly after the same experiment, the hydrophilicity decreased significantly. The coating prepared in Comparative Example 3 is light brown. Although the surface color also showed obvious shedding changes after the same experiment, the surface wettability was also significantly reduced. In contrast, the coating prepared in Example 1 can maintain its color, and the corrosive solution remains colorless, which indicates that the titanium dioxide nanoarmor has good corrosion resistance.
[0107] from Fig.13 and Fig.14 It can be seen that the film of the present invention maintains its super hydrophilicity and underwater super oleophobicity after immersion, the water contact angle in air is less than 25.5 degrees, and the contact angle of oil underwater exceeds 155 degrees. In addition, after these stability evaluations, a large number of titanium dioxide nanoparticles are still evenly distributed on the surface of the coating prepared in Example 1 without obvious loss. Therefore, the coating prepared by the present invention also has excellent stability in a corrosive environment, which further broadens its potential application in a corrosive environment.
[0108] Test Example 5
[0109] The coating prepared in Example 1 was tested for its ability to separate oil-in-water emulsions. The results are as follows: Fig.16 and Fig.17 As shown. Fig.16 It can be seen that after filtration through the modified membrane prepared in Example 1, almost all widely distributed oil droplets in the milky white cyclohexane-in-water (C / W) emulsion were cleaned to obtain a transparent and clear filtrate. In addition to cyclohexane, various SDS-stabilized emulsions were studied, such as n-hexane (N / W), petroleum ether (P / W), hexadecane (H / W) and diesel (D / W). Fig.17 It can be seen that the permeation flux of the modified membrane prepared in Example 1 for various emulsions is greater than 3370.88 L m -2 h -1 bar -1 The corresponding oil rejection rates are 99.71%, 99.53%, 99.67%, 99.40% and 99.46%, respectively. Therefore, the modified membrane prepared in Example 1 exhibits excellent oil repellency, indicating that it can be effectively used to separate surfactant-stabilized emulsions. Since the water wettability and underwater oleophobicity of Comparative Examples 1-4 are not good, Comparative Examples 1-4 cannot efficiently separate cyclohexane-in-water emulsions.
[0110] Test Example 6
[0111] The photocatalytic self-cleaning performance of the coatings prepared in Example 1, Comparative Example 1 and Comparative Example 3 was tested. The SDS-stabilized diesel-in-water emulsion was used as the research object, and the modified membrane prepared in Example 1 was used for separation. During the cycle, a comparative experiment was conducted using a self-cleaning regeneration method using ultraviolet light irradiation or a method using pure water rinsing only. Through ATR-FTIR testing, it was found that after dozens of cycles, due to diesel contamination, the peaks belonging to the vibration of -CH3 and -CH2 were stronger, and the intensities of other characteristic peaks were weakened. However, after the contaminated membrane was irradiated with ultraviolet light for 4 hours, these characteristic peaks returned to normal. But at 3100-3600cm -1 The broad peak at the film is stronger than that before contamination, which may be due to the generation of hydroxyl radicals after ultraviolet light irradiation. It can be seen that the coating prepared in Example 1 has excellent self-cleaning performance. Since the diesel-in-water emulsion cannot be separated in Comparative Examples 1 and 3, the surface will be completely contaminated by oil droplets. In addition, there are too few titanium dioxide nanoparticles on the surface of Comparative Examples 1 and 3, resulting in the inability of photocatalytic self-cleaning.
[0112] Test Example 7
[0113] The anti-fog performance of the goggles coated with the coating prepared in Example 9 was tested. The coating prepared by the present invention did not significantly attenuate the light transmittance of the goggles, and no large amount of water fog was generated on the lenses when the modified goggles were worn for a long time, and the vision was not affected at all times. Therefore, the composite coating of the present invention has application potential in the anti-fog field.
[0114] It should be noted that the above embodiments and test examples are only partial embodiments of the present invention and corresponding test results. By changing parameters such as time and temperature, and changing oxidants, organic solvents, etc., the composite coating prepared by the preparation method of the present invention still has the characteristics of corrosion resistance, self-cleaning and super wetting.
[0115] In summary, the composite coating of the present invention has the characteristics of super-wetting, that is, super-hydrophilic in air and super-oleophobic underwater; has the characteristics of corrosion resistance, that is, it can resist chemical corrosion; has the characteristics of self-cleaning, that is, it can photocatalytic self-cleaning. The coating applied to the surface of porous media can be used for separation of oil-water layered mixtures, corrosive oil-water layered mixtures, surfactant-stabilized water-in-oil emulsions, and surfactant-stabilized corrosive water-in-oil emulsions; the coating applied to the surface of dense media can prevent fogging. Compared with the prior art, the present invention has significant progress.
[0116] The above description is only a preferred embodiment of the present invention and does not constitute any form of limitation to the present invention. Although the present invention has been disclosed as a preferred embodiment as above, it is not intended to limit the present invention. Any technician familiar with the profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a corrosion-resistant, self-cleaning and super-wetting composite coating, characterized in that: The following steps are involved: S1: preparing a substrate material, a bionic adhesive coating and a bionic mineralized coating; the bionic adhesive coating is an aqueous solution of gallic acid and / or a gallic acid derivative compound and an oxidant, and the bionic mineralized coating is a solution of n-butyl titanate diluted with an organic solvent; S2: immersing the base material in the bionic adhesive coating, taking it out, washing it, and drying it to obtain a base material coated with a polyphenol molecular bridge; S3: immersing the base material coated with the polyphenol molecular bridge in the bionic mineralization coating, taking it out, washing it, and drying it to obtain the composite coating.
2. The method for preparing the corrosion-resistant, self-cleaning and super-wetting composite coating according to claim 1, characterized in that: In step S1, the concentration of the gallic acid and / or gallic acid derivative compound in the aqueous solution is 0.05-10 mg / mL, and the concentration of the oxidant in the aqueous solution is 0.05-5 mg / mL.
3. The method for preparing the corrosion-resistant, self-cleaning and super-wetting composite coating according to claim 2, characterized in that: The oxidant is an inorganic oxidant.
4. The method for preparing the corrosion-resistant, self-cleaning and super-wetting composite coating according to claim 3, characterized in that: The inorganic oxidant is an oxygen-containing acid of a halogen and its salts or peroxyacids.
5. The method for preparing the corrosion-resistant, self-cleaning and super-wetting composite coating according to claim 1, characterized in that: In step S1, the concentration of the solute in the n-butyl titanate solution is 0.01-10 mg / mL.
6. The method for preparing the corrosion-resistant, self-cleaning and super-wetting composite coating according to claim 5, characterized in that: The organic solvent is one or more of anhydrous methanol, anhydrous ethanol, n-hexane, cyclohexane, petroleum ether or oleic acid.
7. The method for preparing the corrosion-resistant, self-cleaning and super-wetting composite coating according to claim 1, characterized in that: In step S2 and step S3, when washing is performed, water and ethanol are used to repeatedly wash several times.
8. The method for preparing the corrosion-resistant, self-cleaning and super-wetting composite coating according to any one of claims 1 to 7, characterized in that: In step S1, when preparing the base material, a step of cleaning the base material is also included.
9. A corrosion-resistant, self-cleaning and super-wetting composite coating, characterized in that: The composite coating is prepared by the method for preparing the corrosion-resistant, self-cleaning and super-wetting composite coating as described in any one of claims 1 to 8.
10. Application of the corrosion-resistant, self-cleaning and super-wetting composite coating as claimed in claim 9 in ecological protection, biomedicine and petrochemical industry.
